The Disposable Author: How Pharmaceutical Marketing Is Embraced within Medicine's Scholarly Literature - Matheson, Alastair (The Hastings Center report, 2016)
The best studies on the relationship between pharmaceutical corporations and medicine have recognized that it is an ambiguous one. Yet most scholarship has pursued a simpler, more saleable narrative in which pharma is a scheming villain and medicine its maidenly victim. In this article, I argue that such crude moral framing blunts understanding of the murky realities of medicine's relationship with pharma and, in consequence, holds back reform. My goal is to put matters right in respect to one critical area of scholarly interest, the medical journal publication. Pharma relies on peer advocacy to sell its wares to prescribing doctors. This is an arrangement in which clinicians’ qualified colleagues, including “key opinion leaders,” are recruited by pharmaceutical corporations and marketing agencies to deliver commercially expedient content to their professional fellows. Precisely how this practice works in the setting of publications is not well understood because ethicists studying the problem have made too much of the narrative of corporate villainy and medical victimhood. Accordingly, criticism of industry publications has been preoccupied with the crudely dishonest practices of ghostwriting, ghost authorship, and “ghost management,” vices condemned as “dirty little secrets” perpetrated from “behind the scenes” with the connivance of academic “shills” or “guest authors,” in contempt of standards set by the International Committee of Medical Journal Editors. This account is appealing, and yet it is wrong or, at the very least, seriously incomplete, with only limited relevance to the actualities of contemporary industry practices. In truth, many commercial publications are not developed in secret but fashioned within a culture of open collaboration, where academic authors make substantial, independent contributions; pharmaceutical companies are showcased rather than hidden; and medicine's editorial standards assist rather than impede the workings of commerce.